Registry Research Funding of the German Society of Plastic, Reconstructive and Aesthetic Surgeons (DGPRÄC) and Research Funding Report 2017/2018 - Giunta, R. E.; Moellhoff, N.; Horch, Raymund E.; Prantl, L.; Beier, J. P.; Daigeler, A.; Dragu, Adrian; Eisenhardt, S. U.; Fuchs, P. C.; Germann, G.; Hirsch, T.; Infanger, M.; et al. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
This report serves to publicize the research of academic institutions for Plastic Surgery within our society DGPRÄC in 2017/2018 and sequels the funding report of 2015/2016. Applications to public, non-public, or industrial funding organizations were evaluated. At the same time, this paper analyses the number of approved DFG applications in Plastic, Thoracic and Vascular Surgery in the GEPRIS system. Contrary to these specialties, Plastic Surgery is not classified as an independent speciality in the subject structure of the DFG review board which results in a lack of transparency concerning Plastic Surgery research work.Our previously established online database (https://docs.google.com/forms/d/1OaSnHyKTysawiI1ie7kfUxDf7nJP_RiTUJTsnb7Mq_E/edit) for reporting requested/ approved and rejected research applications to public, non-public and industrial funding organizations was continued and evaluated together with applications found in the DFG's public database GEPRIS.Compared to the previous year's report, the number of approved applications from public research organizations (DFG, BMBF, BMWi, EU) was increased from 23 to 27. We identified 19 approved DFG applications from Plastic Surgery, as compared to 9 and 8 applications by Thoracic and Vascular Surgery, respectively.Taken together, this data emphasizes that our research is at least equal to that of other newly established surgical specialties within the framework of the DFG. Accordingly, we hope to provide further arguments for an adaptation of the DFG review boards subject structure to include Plastic Surgery as an independent specialty as it is for Vascular Surgery and Thoracic Surgery.
EVALuna2:50995